(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study is aimed at exploring the knowledge, attitude, and practice (KAPs) concerning chicken coccidiosis and to examine the usage of anticoccidials among poultry farmers in Kwara State, Nigeria. Information accessing the KAPs of chicken coccidiosis and its control was collected from one hundred and twenty-three poultry farmers using a semi-structured questionnaire. More number of farmers (121/123; 98.37%) had knowledge about chicken coccidiosis, with 16.26% of them documenting that it is caused by a protozoan. Higher number of the farmers believed chicken coccidiosis is economically important, preventable and treatable. More number of farmers (n = 106, 86.18%) had previously used anticoccidials in their farm compared to those that had not 17 (13.82%). The thiamine analogue alone of anticoccidial was the most used drug (n = 27, 25.47%; 95% CI = 18.14 – 34.52) used by farmers. The frequency of anticoccidial drug usage by farmers decreased as the number of drugs being used increased. Data from this study will assist the government and other relevant stakeholders in identifying areas where farmers in Kwara State need to improve their knowledge, attitude, and practice concerning chicken coccidiosis for more effective disease management and improved productivity.